Ponderosa : Big Pine of the Southwest - Allred, Sylvester, 1946- (Book collections on Project MUSE., 2015)
"This manuscript examines the ponderosa pine forests of the US Southwest (Arizona, Colorado, New Mexico, and Utah) by describing the author's observations as he walks through the forests around his home in Flagstaff, Arizona. It discusses the basic history of ponderosa pines, their range from Canada to Mexico, and the plant and animal life found in these forests"--Provided by publisher.